2011
DOI: 10.1007/s00134-011-2189-1
|View full text |Cite
|
Sign up to set email alerts
|

Can procalcitonin help identify associated bacterial infection in patients with severe influenza pneumonia? A multicentre study

Abstract: PCT may help discriminate viral from mixed pneumonia during the influenza season. Levels of PCT less than 0.8 μg/l combined with clinical judgment suggest that bacterial infection is unlikely.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
82
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(91 citation statements)
references
References 16 publications
(16 reference statements)
3
82
1
5
Order By: Relevance
“…High statistical heterogeneity of the included studies ( I 2  = 95%) removed confidence in reporting an estimate of the pooled mean proportion of bacterial coinfection through meta‐analysis. Using Cook's distances to identify studies that most greatly affected the heterogeneity and results, we found that seven studies contributed more than 50% of the heterogeneity 29, 31, 34, 39, 40, 45, 46. The proportion of bacterial coinfection among the remaining 20 studies, representing 64% of all patients, was between 11% and 35% ( I 2  = 37%).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…High statistical heterogeneity of the included studies ( I 2  = 95%) removed confidence in reporting an estimate of the pooled mean proportion of bacterial coinfection through meta‐analysis. Using Cook's distances to identify studies that most greatly affected the heterogeneity and results, we found that seven studies contributed more than 50% of the heterogeneity 29, 31, 34, 39, 40, 45, 46. The proportion of bacterial coinfection among the remaining 20 studies, representing 64% of all patients, was between 11% and 35% ( I 2  = 37%).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 27 articles encompassing 3215 patients met all the inclusion criteria and were included in the final analysis 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54. Of those 27, only eight studies, with 334 patients, provided the numbers or percentages of each bacterial coinfecting pathogen 28, 32, 33, 34, 38, 43, 46, 47. Thus, these eight studies formed the basis for identifying the most common coinfecting bacterial pathogens (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The median age of those with bacterial coinfection was 43 years, and the mortality rate was 21%. In this setting, procalcitonin levels of Ͼ0.8 g/liter had a sensitivity of 91% for detecting bacterial coinfection (729). However, previously well patients with influenza virus infections are not the only patient group affected by PVL-positive necrotizing pneumonia: in a retrospective review of 15 patients with CA-MRSA CAP, only 1 had evidence of preceding influenza, there was no seasonal pattern, and half of the patients were immunocompromised.…”
Section: Clinical Features and Outcomesmentioning
confidence: 97%
“…Staphylococcal PVL-positive necrotizing pneumonia was initially described in young, previously healthy patients with a preceding flu-like illness, with rapid onset of severe symptoms, high fever, leukopenia, cavitary pneumonia, and a fulminant course with mortality rates of 56% (727,728). During the 2009 influenza A virus H1N1 pandemic in France, among 103 patients admitted to the ICU with confirmed influenza A virus H1N1 2009 infections, 48 had bacterial coinfection (54% due to Streptococcus pneumoniae and 31% due to S. aureus) (729). The median age of those with bacterial coinfection was 43 years, and the mortality rate was 21%.…”
Section: Clinical Features and Outcomesmentioning
confidence: 99%